The Use of Podcasts among University Students in Learning English Vocabulary - Musdalipah Musdalipah; La Sunra; Geminastiti Sakkir (PT Ahan Group Publisher, 2026)
This study aims to describe how students use podcasts to learn vocabulary and to explore their perceptions of using podcasts in vocabulary learning. This study employed a descriptive qualitative research design. Data were collected through semi-structured interviews with ten students from the English Language Education Study Program at Universitas Negeri Makassar, selected using purposive sampling. The findings reveal that students use podcasts flexibly, either for focused learning or during daily activities, and they gain new vocabulary through exposure to authentic language.